2-Clorodeoxyadenosine in therapy of children with Langerhans cell histiocytosis - G. G. Solopova; D. D. Baidildina; L. I. Zharikova; I. I. Kalinina; U. N. Petrova; Ye. V. Suntsova; O. V. Goronkova; L. A. Hachatryan; V. V. Sinitsina; G. A. Novichkova; A. A. Maschan; M. A. Maschan (Онкогематология)
Standard therapy of high risk patients with Langerhans cell histiocytosis (LCH) is associated with essential risk of therapy failure. In the present study results of 2-clorodeoxyadenosine usage as alternative therapy in this group of patients are analyzed. In this study 31 patients with multisystem form LCH with involving of organs at risk were included. Nineteen patients have received Prednisone and Vinblastine as front line therapy (standard group). Nine patients have received therapy with 2-CdA and cytosine-arabinoside (group 2-CdA). The patients in standard group statistically significant more often (55.5 % vs. 0 %, р = 0.0095) required second line therapy. Permanent disease conse-quences was more often developed in standard group (63.6 % vs. 0 %, р = 0.0147). The overall survival was 65.7 ± 12,8 % among standard group patients and 88.8% ±10% in 2-CdA group; p = 0.27. The event-free survival was in standard group 33.9 ± 12 %, in 2-CdA group – 88.8 ± 10 %, p = 0.0207. Severe hematological toxicity was observed at 2-CdA therapy. 2-CdA therapy is highly effective in treatment of high risk patients with LCH. The drug should be used only in a specialized hospital.